The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2013
DOI: 10.1128/aem.03987-12
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Removal by a Nitritation-Anammox Bioreactor at Low Temperature

Abstract: dCurrently, nitritation-anammox (anaerobic ammonium oxidation) bioreactors are designed to treat wastewaters with high ammonium concentrations at mesophilic temperatures (25 to 40°C). The implementation of this technology at ambient temperatures for nitrogen removal from municipal wastewater following carbon removal may lead to more-sustainable technology with energy and cost savings. However, the application of nitritation-anammox bioreactors at low temperatures (characteristic of municipal wastewaters except… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
136
4
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 262 publications
(155 citation statements)
references
References 46 publications
(39 reference statements)
12
136
4
3
Order By: Relevance
“…This indicates that the optimum temperature, for anammox biomass cultivated at 30°C, 25°C and 20°C, is equal to or higher than the maximum temperature (=30°C) tested in these experiments. A change in temperature optimum for anammox bacteria, cultivated at different temperatures, has been reported in literature for a C. Brocadia fulgida-like strain and a marine anammox strain [29,35]. Nonetheless, this observation was not confirmed in other studies [34].…”
Section: Combination Of Long-and Short-term Effect Of Temperaturementioning
confidence: 83%
“…This indicates that the optimum temperature, for anammox biomass cultivated at 30°C, 25°C and 20°C, is equal to or higher than the maximum temperature (=30°C) tested in these experiments. A change in temperature optimum for anammox bacteria, cultivated at different temperatures, has been reported in literature for a C. Brocadia fulgida-like strain and a marine anammox strain [29,35]. Nonetheless, this observation was not confirmed in other studies [34].…”
Section: Combination Of Long-and Short-term Effect Of Temperaturementioning
confidence: 83%
“…Although the measurement of the organic matter content in the influent and effluent of the SBR-Anammox system was not performed, the previous characterization of the pretreated pig slurry used to fed the CSTR-partial nitritation reactor indicated that some slowly biodegradable organic matter was present (around 100 mg C·L -1 ) which could be used for denitrification. Another reason of the lower nitrate production respect to the ammonia consumption could be attributed also to the moderate temperatures, since Hu et al [10] observed that the NO 3 -/NH 4 + ratio for the anammox bacteria in a nitritation-anammox SBR decreased from 0.18 to 0.04 when the operational temperature was decreased from 25 to 12 °C.…”
Section: Anammox Processmentioning
confidence: 99%
“…Despite the fact that the optimum performance of Anammox bacteria is obtained at 30-40 ºC [8], some studies demonstrated that it is possible the operation of Anammox systems at lower temperatures [9][10][11]. In fact this occurs naturally in the environment, since Anammox bacteria have been detected in various marine and freshwater mediums at low temperatures [12].…”
Section: Introductionmentioning
confidence: 99%
“…If they were not completely lysed after incubation, the lysozyme-treated cells were pelleted by centrifugation for 5 min at 1,200 ϫ g. Then, the pellet was washed with 10 ml of synthetic medium (37) without substrates 3 times or until it was free of EDTA and lysozyme. The cells were resuspended in 10 ml synthetic medium containing 2 mM ammonium and nitrite, followed by anammox activity tests, as previously described (38), with modifications. In short, 10 ml cells was transferred to a 30-ml serum bottle after the pH was adjusted to 7.3.…”
Section: Methodsmentioning
confidence: 99%